Therapy of Chronic Viral Hepatitis - Siti Nurdjanah (The Indonesian Society for Digestive Endoscopy, 2001)
Chronic hepatitis due to hepatitis B virus (HBV) or hepatitis C virus (HCV) is still a major problem in terms of progressive liver damage, prevention and therapy in most parts of the world. Unfortunately, to date, there is still no specific and effective therapy for HBV. No therapy can be given to carrier, non- replicative and asymptomatic patients of chronic HBV infection. Lamivudine or alpha-interferon can be used for treatment of compensated, chronic hepatitis B infection with significant increase of aminotransferase. Approximately 40 % of patients can have seroconversion with this form of therapy. Chronic hepatitis D virus infection can be treat with alpha-interferon and in the final stage, may undergo liver transplantation. For chronic hepatitis C virus infection, alpha-interferon with ribavirin have been shown to have a better efficacy than alpha-interferon alone where the efficacy can reach 39 – 49 %. Keywords: hepatitis, interferon, lamivudin,ribavirin